Explorando as Funções Quadráticas: Estratégias e Atividades Práticas para o Ensino Efetivo - DANILO TADASHI IZUMITANI (2023)
The study of quadratic functions is one of the concepts present in the National Common Curricular Base (BNCC) for high school students. This work aims to show the reader an activity carried out with students from a state school in the interior of São Paulo with the purpose of developing the skills EM13MAT402 and EM13MAT502, using the launch of a basketball in the school court, as well as demonstrations and the use of the Tracker and GeoGebra software.